2013
DOI: 10.1117/1.jbo.18.11.111405
|View full text |Cite
|
Sign up to set email alerts
|

Real-time suppression of turbidity of biological tissues in motion by three-wave mixing phase-conjugation

Abstract: To cite this version:Fabrice Devaux, Éric Lantz. Real-time suppression of turbidity of biological tissues in motion by three-wave mixing phase-conjugation. Journal of Biomedical Optics, Society of Photo-optical Instrumentation Engineers, 2013, 18, pp.111405. Real time suppression of turbidity of biological tissues in motion by three-wave mixing phase conjugation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…We show that, while the incident light is strongly depolarized on the whole, the light that reaches the output face of the scattering medium is much less depolarized. This simple fact could explain the results reported in [1].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…We show that, while the incident light is strongly depolarized on the whole, the light that reaches the output face of the scattering medium is much less depolarized. This simple fact could explain the results reported in [1].…”
Section: Introductionsupporting
confidence: 58%
“…For a radius r s = 0.9λ and a refractive index of the non-absorptive dielectric spheres n s = √ ε s = 1.34, the size parameter of the spheres is kr s = 2πn s r s λ = 7.6, which implies that light scattering occurs in the Mie regime, with an anisotropy coefficient g = 0.85. Although the scattering properties of a medium mostly depend on the relative size of the spheres with respect to the wavelength, we perform calculations by considering a wavelength λ = 1µm corresponding approximately to the wavelength used in our experiments reported in [1]. Considering that spheres are embedded in a lossless homogeneous medium with a refractive index n m = √ ε m = 1 and with volume concentrations of 5%, 7%, 9% and 11%, the scattering coefficients are calculated using the Mie theory.…”
Section: Time-resolved Propagation Of a Short Pulse In Scattering Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, we have shown that the signal to noise ratio (SN R) in the restored image is improved significantly thanks to a motion of the scattering medium during the acquisition time. 15 Indeed, in this case, uncorrelated speckle patterns are summed by the camera during the acquisition time. Then, this speckle averaging reduces the intensity fluctuations and therefore improves the SN R of the PC images.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…15 These results indicate that the scattering process in such biological samples is more or less independent of the polarization state of the light and that a polarization change of the phase conjugate (PC) wave with respect to the incident wave does not preclude the image restoration process. Indeed, because in a type 2 TWM interaction the phase matching condition implies that the signal and the idler waves are polarized in orthogonal directions, the PC wave (i.e.…”
Section: Introductionmentioning
confidence: 91%